Excision of Intra-articular Knee Heterotopic Ossification Using a 70° Arthroscope - Alexander J. Hoffer; Eugenia A. Lin; Maziyar A. Kalani; Mark K. Lyons; Meghan Richardson (Case Reports in Orthopedics)
Heterotopic ossification is ectopic lamellar bone formation within soft tissue and can result in significant functional limitations. There are multiple underlying etiologies of HO including musculoskeletal trauma and traumatic brain injury. Intra-articular HO of the knee is rare and is typically located within the cruciate ligaments. We report a case of a 24-year-old female who presented with worsening right knee pain and limited knee extension two and a half years after a motor vehicle crash with multiple lower extremity fractures. Physical examination of the knee revealed anterior pain, limited extension, and a palpable infrapatellar prominence. Imaging showed a retropatellar tendon, intra-articular excrescence of bone proximal to the anterior tibial plateau. Diagnostic arthroscopy with a 70° arthroscope identified HO at the proximal anterior tibial plateau, which was excised with a high-speed burr under direct visualization. At the three-month follow-up, the patient remained asymptomatic and returned to sport. Retropatellar tendon, intra-articular anterior knee HO is a rare but debilitating clinical entity that can be successfully and safely managed with excision under direct visualization using a 70° arthroscope.